2021
DOI: 10.1136/annrheumdis-2021-220049
|View full text |Cite
|
Sign up to set email alerts
|

Use of Janus kinase inhibitors in COVID-19: a prospective observational series in 522 individuals

Abstract: To cite Melikhov O, Kruglova T, Lytkina K, et al. Ann Rheum Dis Epub ahead of print: [please include Day Month Year].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…Zhu et al [ 14 ] reported on tofacitinib treatment of refractory cutaneous leukocytoclastic vasculitis. In infectious diseases, Tatiana [ 15 ] reported that tofacitinib was effective in 320 patients with COVID-19; this study evaluated a prospective observational series. Tong found that tofacitinib reduced death or respiratory failure at 28 days in patients hospitalized with COVID-19 pneumonia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 14 ] reported on tofacitinib treatment of refractory cutaneous leukocytoclastic vasculitis. In infectious diseases, Tatiana [ 15 ] reported that tofacitinib was effective in 320 patients with COVID-19; this study evaluated a prospective observational series. Tong found that tofacitinib reduced death or respiratory failure at 28 days in patients hospitalized with COVID-19 pneumonia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baricitinib is a Janus associated kinase (JAK) inhibitor, which was primarily used for treatment of rheumatoid arthritis [49][50][51]. It has a good safety and efficacy profile, despite some concerns [52][53][54][55]. Baricitinib is able to modulate the cytokine storm through the JAK-STAT pathway [56][57][58][59][60][61][62].…”
Section: Baricitinib Olumiant®mentioning
confidence: 99%
“…In this themed issue of the Annals of the Rheumatic Diseases, focused on COVID-19 and SARS-CoV-2 vaccination in rheumatology, a number of papers have been assembled, which advance our understanding in this area and should allow for optimising the approach to this pandemic in the near future. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] To date, our understanding of COVID-19 risk in rheumatology comes primarily from observational registry-based cohorts. A clear signal has emerged in that patients receiving B-cell depletion therapy or high-dose glucocorticoids at baseline are at higher risk of more severe COVID-19 outcomes if infected.…”
Section: Editorialmentioning
confidence: 99%